Odpowiedzi

2010-01-20T15:07:07+01:00
A)4c-(3c+2)-10c=
= 4c-3c-2-10c = -11c-2

b)7x-8-(5x+6)=
= 7x-8-5x-6 = 2x-14

c)9y-(8-3y)+16=
= 9y-8+3y+16 = 12y+8

d)5x-(2-4x)+8x-7=
=5x-2+4x+8x-7 = 17x-9

e)-(-5c-8)+6-9c-c=
= 5c+8+6-9c-c = -5c+14

f)-4(3x-6)-3(2+7x)=
= -12x+24-6-21x = -32x+18

g)5(3z-7)-9(-8z-6)=
= 15z-35+72z+54 = 87z+19

i)7x-3(5x+2)-6(7+2x)=
= 7x-15x-6-42-12x = -20x - 48
2010-01-20T15:07:45+01:00
A) 4c-3c-2-10c = -9c-2
b) 7x-8-5x-6 = 2x-14
c) 9y-8+3y+16 = 12y+8
d) 5x-2+4x+8x-7 = 17x-9
e) 5c +8+6-9c-c = -5c+14
f) -12x+24-6-21x = -33x+18
g) 15z-35+72z+54 = 87z +19
i) 7x-15x-6-42-12x = -20x-48
2010-01-20T15:20:24+01:00
A)=4c-3c-2-10c=-9c-2
b)=7x-8-5x-6=2x-14
c)=9y-8+3y+16=12y+8
d)=5x-2+4x+8x-7=17x-9
e)=5c+8+6-9c-c=-5c+14
f)=-12x+24-6-21x=-33x+18
g)=15z-35+72z+54=87z+19
i)=7x-15-6-42-12x=20x-48